Can Raising Awareness about the Psychological Causes of Obesity Reduce Obesity Stigma?. Issue 5 (4th May 2018) - Khan, Sammyh S.; Tarrant, Mark; Weston, Dale; Shah, Pooja; Farrow, Claire
ABSTRACT: Obesity stigma largely remains a socially acceptable bias with harmful outcomes for its victims. While many accounts have been put forward to explain the bias, the role of obesity etiology beliefs has received little scrutiny. The research examined the effect that beliefs about the psychological etiology of obesity have on the expression of obesity stigma and the mechanisms underpinning this effect. Participants ( N  = 463) were asked to evaluate a target person with obesity after reading one of three possible etiologies: psychological, genetic, or behavioral. The presentation of a psychological etiology of obesity elicited less prejudice compared to behavioral causes but greater prejudice compared to genetic causes; observed differences were found to be a function of the agency ascribed to the target's obesity and empathy expressed for the target. The findings highlight the impact that communicating obesity in terms of psychological causes can have for the expression of obesity stigma.